McbG, a LysR Family Transcriptional Regulator, Activates the mcbBCDEF Gene Cluster Involved in the Upstream Pathway of Carbaryl Degradation in Pseudomonas sp. Strain XWY-1 - Ke, Zhijian (Appl Environ Microbiol, 2021)
Although enzyme-encoding genes involved in the degradation of carbaryl have been reported in Pseudomonas sp. strain XWY-1, no regulator has been identified yet. In the mcbABCDEF cluster responsible for the upstream pathway of carbaryl degradation (from carbaryl to salicylate), the mcbA gene is constitutively expressed, while mcbBCDEF is induced by 1-naphthol, the hydrolysis product of carbaryl by McbA. In this study, we identified McbG, a transcriptional activator of the mcbBCDEF cluster. McbG is a 315-amino-acid protein with a molecular mass of 35.7 kDa. It belongs to the LysR family of transcriptional regulators and shows 28.48% identity to the pentachlorophenol (PCP) degradation transcriptional activation protein PcpR from Sphingobium chlorophenolicum ATCC 39723. Gene disruption and complementation studies reveal that mcbG is essential for transcription of the mcbBCDEF cluster in response to 1-naphthol in strain XWY-1. The results of the electrophoretic mobility shift assay (EMSA) and DNase I footprinting show that McbG binds to the 25-bp motif in the mcbBCDEF promoter area. The palindromic sequence TATCGATA within the motif is essential for McbG binding. The binding site is located between the –10 box and the transcription start site. In addition, McbG can repress its own transcription. The EMSA results show that a 25-bp motif in the mcbG promoter area plays an important role in McbG binding to the promoter of mcbG. This study reveals the regulatory mechanism for the upstream pathway of carbaryl degradation in strain XWY-1. The identification of McbG increases the variety of regulatory models within the LysR family of transcriptional regulators. IMPORTANCE Pseudomonas sp. strain XWY-1 is a carbaryl-degrading strain that utilizes carbaryl as the sole carbon and energy source for growth. The functional genes involved in the degradation of carbaryl have already been reported. However, the regulatory mechanism has not been investigated yet. Previous studies demonstrated that the mcbA gene, responsible for hydrolysis of carbaryl to 1-naphthol, is constitutively expressed in strain XWY-1. In this study, we identified a LysR-type transcriptional regulator, McbG, which activates the mcbBCDEF gene cluster responsible for the degradation of 1-naphthol to salicylate and represses its own transcription. The DNA binding site of McbG in the mcbBCDEF promoter area contains a palindromic sequence, which affects the binding of McbG to DNA. These findings enhance our understanding of the mechanism of microbial degradation of carbaryl.